2021
DOI: 10.3390/ma14185262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cerium on the Microstructure and Inclusion Evolution of C-Mn Cryogenic Vessel Steels

Abstract: The effects of Cerium (Ce) were studied on the casting slab quality, microstructure, and inclusion evolution of cryogenic vessel steel. An optical metallographic microscope, scanning electron microscope, energy dispersive spectrometer, and Thermo-calc thermodynamic software were used for characterization and analysis. The results indicated that the central segregation was significantly improved after adding Ce and reached the lowest level when the content of Ce was 0.0009 wt.%. Meanwhile, the presence of Ce re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The inclusions of 55SiCrA spring steel were identified to be Al 2 O 3 –SiO 2 , CaO–Al 2 O 3 –SiO 2 , MgO–CaO–Al 2 O 3 –SiO 2 , and MnS. Some studies have shown MnS precipitates during solidification process, [ 30,31 ] which are related to the cooling rate, and S and Mn contents in steel. [ 32,33 ] In this study, the analysis and discussion are focused on the evolution of the oxide inclusions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusions of 55SiCrA spring steel were identified to be Al 2 O 3 –SiO 2 , CaO–Al 2 O 3 –SiO 2 , MgO–CaO–Al 2 O 3 –SiO 2 , and MnS. Some studies have shown MnS precipitates during solidification process, [ 30,31 ] which are related to the cooling rate, and S and Mn contents in steel. [ 32,33 ] In this study, the analysis and discussion are focused on the evolution of the oxide inclusions.…”
Section: Resultsmentioning
confidence: 99%
“…MnS. Some studies have shown MnS precipitates during solidification process, [30,31] which are related to the cooling rate, and S and Mn contents in steel. [32,33] In this study, the analysis and discussion are focused on the evolution of the oxide inclusions.…”
Section: Andmentioning
confidence: 99%
“…As a result, the criteria for cryogenic vessel steels have become increasingly stringent. [1][2][3] The choice of steel for cryogenic vessels necessitates high strength, high ductility, and exceptional low-temperature toughness. [4,5] To date, the most extensively studied cryogenic vessel material is nickel steel.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, calcium, rare earths, etc. were utilized to promote the formation of fine sulfides which are more stable and have a higher melting point than that of manganese sulfides [13][14][15]. Imagumbai et al [16] proposed that the quantity of MnS inclusions increased with the increase in cooling rate, while the average size decreased.…”
Section: Introductionmentioning
confidence: 99%